AB0885 The Burden of Osteoporotic Hip Fractures in Portugal: Costs, Quality of Life and Mortality. (9th June 2015) - Marques, A.A.; Lourenço, Ó.; Pereira da Silva, J.A.
Abstract : Background: Osteoporotic fractures represent a remarkable burden to health care systems and societies worldwide, which will tends to increase as life expectancy expands and life style changes favour osteoporosis (1). The cost-effectiveness evaluation of intervention strategies demands accurate data on the epidemiological and economical reality to be addressed (2). Objectives: To estimate the overall societal cost of hip fractures, the per-patient costs and the impact on quality of life in Portugal, based on real-life individual patient data. Methods: Information was collected on consumption of health resources, quality of life and mortality regarding 186 patients randomly selected to represent the distribution of hip fractures in the Portuguese population, in terms of gender, age and geographical provenience. Data were cross-tabulated with socio-demographic variables and individual resources consumption to estimate the burden of disease. A societal perspective was adopted, including direct and indirect costs. Multivariate analyses were carried out to assess the main determinants of Heath-related Quality of Life. Results: Mean individual fracture-related costs were estimated at € 13, 434 for the first year and € 5, 985 for the second year following the fracture. In 2011 the economic burden attributable to osteoporotic hip fractures in Portugal could be estimated at € 216. Mean reduction in quality of life 12 months after fracture was estimated at 0.34. Regression analysis showed that age was associated with a higher loss of HrQoL, whereas education had the opposing effect. We observed an excess of 12% in mortality in the 2 first year after hip fracture, when compared to the gender and age-matched general population. Conclusions: Results of this study indicate that osteoporotic hip fractures are associated with a high societal burden, in terms of costs, loss in quality of life and mortality. These data provide valuable input to the design and selection of fracture prevention strategies. References: Hernlund E, Svedbom A, Ivergard M, Compston J, Cooper C, Stenmark J, et al. Osteoporosis in the European Union: medical management, epidemiology and economic burden. A report prepared in collaboration with the International Osteoporosis Foundation (IOF) and the European Federation of Pharmaceutical Industry Associations (EFPIA). Archives of osteoporosis. 2013;8(1-2):136. Johnell O. The socioeconomic burden of fractures: today and in the 21st century. The American journal of medicine. 1997;103(2a):20S-5S; discussion 5S-6S. Disclosure of Interest: None declared